Intrapartum posterior wall rupture in unscarred uterus during labour augmentation with oxytocin; a case report - Verma, Divya; Kumar, Sanjeev; Sharma, Premveetrag (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Intrapartum rupture of unscarred uterus during labour augmentation is an exceedingly rare occurrence with very few case reports of this entity in the literature. We intend to report such case to highlight the importance of constant vigilance during oxytocin infusion even in patients with unscarred uterus. The 27 years old lady who had a previous normal vaginal delivery, came in early labour at term gestation. Augmentation of labour was done with oxytocin. After 30 mins of starting oxytocin patient complained of severe pain abdomen and on CTG fetal heart dropped to 70 bpm. Despite all measures fetal heart rate did not pick up and patient was taken up for cesarean section. Intraoperatively, posterior uterine wall ruptured was found with baby and placenta lying in the abdominal cavity. Baby had a low Apgar score and died on third day. Uterine rupture repair was done and patient was discharged on 5th postoperative day. Although oxytocin has excellent safety record in unscarred uterus, the possibility of rupture uterus should be kept in mind in relevant clinical scenario.